2021
DOI: 10.1002/lary.29877
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Mandibular Distraction Osteogenesis Among Infants Less Than 3 kg

Abstract: Objectives/Hypothesis Mandibular distraction osteogenesis (MDO) is a safe and effective surgery to address respiratory and feeding issues due to micrognathia in patients with Robin Sequence (RS). Previous studies examining postoperative complications in neonates receiving MDO have considered 4 kg as the cut‐off for low weight; however, an increasing number of MDO interventions are performed in infants <4 kg. To determine if a weight <3 kg at time of MDO is a risk factor for postoperative complications or need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Distraction was performed at a mean age of 35 days, and tracheostomy was necessary in two cases. 8 Analysis of 117 infants with PRS and early mandibular distraction at an average age of 71 days revealed an enlarged upper airway cross section, 9 which was also shown in our case (Fig. 4 ).…”
Section: Discussionsupporting
confidence: 83%
“…Distraction was performed at a mean age of 35 days, and tracheostomy was necessary in two cases. 8 Analysis of 117 infants with PRS and early mandibular distraction at an average age of 71 days revealed an enlarged upper airway cross section, 9 which was also shown in our case (Fig. 4 ).…”
Section: Discussionsupporting
confidence: 83%
“…Approximately 20% of the patients were less than 3 kg at the time of surgery. Logistic regression showed no relationship between the weight at the time of surgery and the presence of a complication or unfavourable outcome [5 ▪▪ ].…”
Section: Surgical Considerationsmentioning
confidence: 86%
“…The complications included device failure, premature ossification, fibrous nonunion, and abscess, but this did not assess feeding outcomes. When specifically evaluating feeding outcomes, Taufique et al 23 found no significant difference in postoperative G-tube rates when comparing infants above and below 3 kg. Alternatively, the results from our institution suggest there may be better G-tube outcomes if infants can reach 3 kg before the time of operation, but definitive interpretation of these results are limited by inability to perform multivariate analysis of our data to assess for the impact of confounding comorbidities.…”
Section: Discussionmentioning
confidence: 99%